The Life Of Poor Madurese Adolescents Left By Their Mothers To Work As International Migrant Workers - Tri Febrianto, Priyono (Opción, 2019)
The study of the lives of the migrant workers’ children is interesting and we reveal the childrearing gathered from the children whose mothers have left to work overseas. This study applied a qualitative approach. The data collec- tion included a large portion of the interviews conducted with 60 families who were international migrant workers in Madura, East Java. This is a region in Indonesia that contributes a vast number of migrant workers. The results of this study revealed that the children of the migrant workers in Madura encountered academic underdevelopment at the hand of the absence of those who supervised their learning at home. They also suffered from loneliness as a result of their incomplete families, friendlessness as they had fewer discussion partners involved in their education proficiency and juvenile delinquency as their family didn’t involve substantial social control.